Pengembangan Bahan Ajar Materi Lempar Lembing Untuk Siswa Sekolah Dasar - Boihaqi - haqi; Dimyati Dimyati; Ermawan Susanto; Hendrifadly Hendrifadly (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
The purpose of this study is to develop teaching materials for javelin throwing materials for elementary school students who have good validity and reliability that can be used in learning, the method in this study is research and developmet, data collection with design validation, product trials, product validation and questionnaire research results show, The results of the validation percentage of the validators obtained answers that validator 1 generally strongly agreed (78.57%) with the design of teaching materials that had been developed by researchers, validator 2 all agreed (100%) with the content of teaching materials developed by researchers, and validator 3 generally strongly agreed (51.79) with the teaching material media that had been developed by researchers. Based on the three validator answers, it can be explained that the four teaching materials, namely: 1) Throw the tailed ball, 2) Turbo throw, 3) Throwing pipes and 4) Modified javelin throwing that was developed already has the feasibility to be taught